Transcriptome reanalysis and gene expression of 13 detoxification genes for avermectin and pyridaben resistance in Panonychus citri - Xiaoqing Han; Mengyuan Peng; Yunlong Zhang; Pan Wu; Xiaoyu Zheng; Xinze Zhang; Shuchen Guo; Yanhong Ding; Na Yang; Meng Li; Yidong Lv; Yi Zhang; et al. (Scientific Reports)
Abstract Citrus red mites (P. citri) are key pests affecting citrus production worldwide due to pesticide resistance. The resistance mechanisms of ten pesticides are known, but a comprehensive study using transcriptome data is missing. This study employed deeptools, cuffdiff, rmats, bcftools and other software to examine gene expression variation, alternative splicing (AS), and mutations in mite resistance. The research highlighted that pesticides can regulate gene transcription, and red mites with resistance increase cytochrome P450, glutathione S-transferases, carboxylesterase, and acetylcholinesterase expression. Pyridaben also induces new AS events. Fluazinam-induced mites show mRNA splicing peaking earlier than transcription, both peaking at one day and returning to baseline after two days. AS profiles are similar in different mite populations with overlapping pesticide resistances. Lastly, specific mitochondrial SNPs in mites might mediate resistance against select pesticides.